Ganciclovir‐induced drug reaction with eosinophilia and systemic symptoms - Shohei Kitayama; Teruhiko Makino; Kuniko Fujita; Shuichi Mori; Fumina Furukawa; Ko Kagoyama; Megumi Mizawa; Tadamichi Shimizu (Wiley, 2023)
Abstract Drug reaction with eosinophilia and systemic symptoms (DRESS) is a severe cutaneous adverse reaction involving multiorgan failure, with a complex interaction of various drugs, human herpesvirus reactivation and immune abnormalities suggested as the aetiology. We herein present the case of a 70‐year‐old man with a one‐week history of fever, facial oedema, erythematous macules and purpura on his trunk and extremities. He had anti‐TIF1γ antibody‐positive dermatomyositis and was treated with prednisolone sodium succinate (20 mg/day). Three weeks earlier, he was treated with ganciclovir (250 mg/day) for 7 days to treat asymptomatic cytomegalovirus viraemia. Laboratory investigations revealed eosinophilia with atypical lymphocytes and elevated liver enzyme levels. A histological examination showed interface dermatitis with necrotic keratinocytes, perivascular infiltration of lymphocytes and eosinophils in the upper dermis and erythrocyte extravasation without vasculitis. A lymphocyte transformation test (LTT) was positive for ganciclovir (stimulation index: 260%; normal: <180%). We diagnosed DRESS caused by ganciclovir on the basis of clinical findings and course (Definite; RegiSCAR score: 7). He was treated with prednisolone sodium succinate (40 mg/day) and topical clobetasol propionate (0.05%) ointment twice daily. After the initiation of treatment, the skin lesions and laboratory abnormalities gradually improved. To our knowledge, this is the first case of DRESS caused by ganciclovir. The patients in whom ganciclovir is used are often immunosuppressed and may be overlooked as the causative drug for DRESS by conventional skin tests. We considered that LTT is useful for identifying causative drugs of DRESS, especially in immunosuppressed patients, such as the present case.